Instruments of support for Polish enterprises' innovativeness - Paulina Nowak (Economic and Environmental Studies (E&ES), 2018)
Innovativeness, as the ability to be innovative in regional, national and global environments, is nowadays the indicator of success in business. Due to rapidly changing environment, business units need to take risky measures in the field of new technologies and manufacturing techniques. Therefore, innovative activity of enterprises is supported by economic policies of countries that aim at achieving high level of innovativeness in their economies. There are various forms of instruments targeted at business units and the instruments themselves are available at various levels (a region, a country, the European Union). Enterprise output innovation may indicate varying regional needs for innovative support from the state. The aim of the article is to systematise the available forms of support for Polish enterprises and to assess regional variations in enterprise output innovation. The assessment includes 16 Polish voivodeships. Secondary information sources, such as statistics provided by the Polish Statistical Office and the Government's reports on entrepreneurship, were used in the article. A review of Polish innovation policy instruments described on the government websites was made in order to systematise the instruments of innovation support. To assess regional output innovation variations (2014-2016), a comparative analysis of indicators such as: innovative enterprises as the share of the total industrial/service enterprises, revenues from sales of new or significantly improved products, was carried out. To define the regions with the structures similar in terms of enterprise output innovation, the agglomerative method of non-linear classification (Ward's method) was applied. The analyses carried out allow systematising the available instruments of enterprise innovativeness support in terms of their sources of financing as well as their division into legal, financial, institutional and infrastructural instruments. The value of public support for innovative activity, in the light of public statistics, differs across regions. The assessment of enterprise output innovation also shows regional differences that seem to result from spatial aspects of development as well as from the size of public contribution. Recognition of these conditionings may have an impact on their effectiveness, while proposing and applying the instruments of Polish innovative policy.
Keywords: O31; O38; R13; 330; innovativeness of enterprises; innovative policy instruments; regional variations